Penerapan Model Socialization, Externalization, Combination and Internalization untuk Pengembangan Knowledge Management System - Deni Mahdiana; Devit Setiono (Prosiding SISFOTEK, 2019)
The Integrated Information and Communication Technology Lab (ICT Lab) at Budi Luhur University is one of the independent institutions that serve laboratory needs for learning as well as Tridarma application within the university. At the moment, the knowledge inside the ICT lab is not yet well distributed so that it tends to rely on one lab assistant who knows the answer to a certain issue. Furthermore, the high turnover causes the ineffectiveness of the assistant’s knowledge distribution due to lack of knowledge management that can further cause knowledge loss because the tacit knowledge is not yet well-documented. Therefore, there needs to be an information system to manage each assistant’s knowledge to foster knowledge sharing. In this research, the author develops a knowledge management system model that fits the needs of the ICT lab through the knowledge formation using Socialization, Externalization, Combination and Internalization (SECI) model. System testing was done using blackbox testing and path analysis approach using Technology Acceptance Model (TAM) model. The result of the knowledge management system’s analysis shows that it support the SECI process in knowledge sharing within the ICT Lab. The test results using 5 variables show scores of above 70% which means the knowledge management system used in this research can be applied to the Integrated ICT Lab of Budi Luhur University.